Chronic nonpigmented Villonodular synovitis in a 13 years old girl: A case report - Masoud Yavari; Naghmeh Pour Pezeshk; Hamidreza Alizadeh Otaghvar; Leili Mohajerzadeh (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Nonpigmented villonodular synovitis is a very uncommon and benign proliferative disorder involving the synovium. It is mostly seen in the knee. Here we present a 13-year old girl with a 2 year history of left wrist mass without any pain, tenderness or limitation in range of motion. We believe it is necessary to considere villonodular synovitis in a child with chronic joint effusion as a differential diagnosis.